Analisis Faktor-Faktor yang Berhubungan dengan Kinerja Pegawai Pada Puskesmas Teluk Lingga Tahun 2024 - Dahlia, Dahlia; Adrianto, Ratno (Jurnal Kesehatan Komunitas, 2024)
Community health centers are pivotal in delivering healthcare services, and it is crucial for them to continually enhance employee performance. The maximum employee headcount of Teluk Lingga Community Health Centre is reflected in the 2021 Community Satisfaction Index (CSI) results as follows: 81.63% in 2021, 81.69% in July 2022, and 81.61% in January 2023. It has yet to attain 100%. This study aims to investigate the factors influencing employee performance. The independent variables identified include organizational climate, work discipline, reward system, employee competence, and physical environment, while the dependent variable is defined as employee performance. An analytical research design employing a cross-sectional approach was utilised. The sample for this study comprises a total of 69 employees from Community health centers in Teluk Lingga. The data analysis used is a chi-square test and multiple logistic regression method. The results of the study are that the influential factors are organisational climate, work discipline, reward system, and employee abilities, which are not related to the physical environment. It is recommended that the provision of appropriate monetary and non-monetary rewards enhances employee performance. Leaders and management should be encouraged to ensure equitable rewards for all employees.